Effect of multi-layer prosthetic foam liner on the stresses at the stumpprosthetic interface - I. Boudjemaa; A. Sahli; A. Benkhettou; S. Benbarek (Fracture and Structural Integrity)
The prosthetic liner plays a significant role in the redistribution of the pressure between the stump and the socket, as adds a cushioning layer between the stump and the socket which relieves pain and makes the prosthesis more comfortable.